PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR SISWA PADA MATERI OPERASI BENTUK ALJABAR - Arni, Wa; Ratumanan, Tanwey Gerson; Huwaa, Novalin Calasin (Program Studi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan Universitas Pattimura, 2023)
This study aims to determine the influence of the Teams Games Tournament (TGT) type cooperative learning model on student learning outcomes on algebraic form operation material. The type of research used is experimental research with a Post-test Only Control Group Design design. The population in this study was all grade VII students of SMP Negeri 21 Ambon which amounted to 73 people from 3 classes. In determining the sample, the Purposive Sampling technique was used, where the sample was students of class VII-1 as an experimental class taught using a cooperative learning model of the Teams Games Tournament (TGT) type and students of class VII-2 as a control class taught using a conventional learning model. The instrument used is a test instrument consisting of 5 description questions. The data analysis techniques used are the Independent Sample T-Test test and the effect test (Effect Size). The results showed that there was a difference in the average student learning outcomes between students who studied with the Teams Games Tournament (TGT) type cooperative learning model and students who studied with conventional learning models. Based on the calculation of the effect size with the cohen’s formula a value of 0,77 is included in the medium category, in applying the cooperative learning model of the teams games tournament (TGT) type it gives a not too high influence on student learning outcomes in algebraic operations material in class VII SMP Negeri 21 Ambon.